Spinal astrocytes involved in the pathogenesis and treatment of neuropathic pain - Li, Xiangmiao; Huang, Yushan; Bai, Jinzhu (Frontiers in Cellular Neuroscience, 2025)
Neuropathic pain is a common and severe type of chronic pain, and its pathogenesis has not been fully defined. Increasing evidence shows that spinal astrocytes play indispensable roles in the occurrence and development of neuropathic pain. Most studies have suggested that activated astrocytes can crosstalk with other glial cells and neurons through morphological and functional changes, exacerbating the development of pain. However, reactive astrocytes have a dual role. As a defense mechanism, reactive astrocytes have roles in increasing neuroprotection and stimulating neurogenesis. Studies have demonstrated a potentially beneficial role for astrocyte activation in neuropathic pain. In addition, the therapeutic mechanisms of multiple drugs and neuromodulatory techniques are thought to be related to astrocytes. This review highlights the recent advances and significance of spinal astrocytes, emphasizing the need for a better understanding of their roles in the pathogenesis and treatment of neuropathic pain.